Research on the driving mechanisms of ecosystem services in the alpine canyon areas of Southwest China - Jiang, Jiahui; Hou, Jian; Zeng, Chen; Feng, Haobo; Zhu, Yufan (Frontiers in Environmental Science, 2025)
The Alpine Canyon Area of Southwest China represents a region of ecological and cultural significance, where multi-ethnic communities rely heavily on ecosystem services for sustenance, including food, water, and other vital resources. To systematically evaluate these dependencies, this study utilized multi-source datasets to quantify the spatiotemporal patterns of four key ecosystem services in the region: carbon sequestration food supply (FS), water yield (WY), and soil conservation (SR). Spearman correlation analysis, geographically weighted regression, and the geographic detector method were employed to analyze trade-offs and synergies among these ecosystem services and explore their driving mechanisms. The results indicated: (1) The four ecosystem services in the study area exhibited significant spatiotemporal heterogeneity. (2) During the study period, the synergies were observed between CS-WY, CS-SR, and WY-SR, highlighting a particularly strong synergy for WY-SR. Conversely, trade-offs were observed for CS-FS, FS-WY, and FS-SR, with the strongest trade-off occurring between food supply and water yield. (3) The trade-offs and synergies among ecosystem services in the region were significantly influenced by a combination of natural and socio-economic factors, with elevation, slope degree, temperature, and population density playing pivotal roles. Among all ecosystem services pairs, the interaction between elevation and other influencing factors represented the most critical driver combination. This study highlights the importance of ecosystem services in multi-ethnic regions, provides insights into ecosystem services trade-offs and synergies, and offers scientific support for regional ecological management.